A multicenter, cross‐sectional analysis to assess the safety and usage pattern of brivaracetam in the management of partial‐onset seizure with BAEs—BREEZE study: A post‐hoc analysis - Arvind Sharma; Krishnaprasad Korukonda; Amit Haldar; Usha Kant Misra; R. V. Anand; Yakshdeep Dave; Girish Kulkarni (Epilepsia Open)
Abstract Objective Brivaracetam (BRV), a third‐generation anti‐seizure medication (ASM) offers strong conformational receptor domain binding, faster blood brain barrier (BBB) permeability and better tolerability making it potential therapeutic option as an initial line or initial line add‐on strategy for focal onset seizure (FoS). The following study was planned to further understand the role and relevance of BRV in the real world settings of India. Method This was a multicentric, cross‐sectional, and non‐interventional study conducted in patients with FoS across India. The study was approved by central independent ethics committee. Descriptive and analytical statistics employed using SPSS version 29.0.1.0. Results Per protocol (PP) analysis included 8479 eligible patients from 1069 sites, gender; 5771 (68.06%) male and 2708 (31.94%) female with mean age 41.21 ± 12.74 years. Total 8019 (94.57%) patients had FoS and 460 (5.43%) patients had focal to bilateral tonic–clonic seizures (FBTCs). In FoS, 4105 (51.19%) patients switched from LEV to BRV whereas 3914 (48.81%) switched from other ASMs to BRV. BAEs accounted for 2059 (50.16%) patients in LEV to BRV switch versus 133 (3.39%) in other ASM to BRV switch. Post switch, LEV‐associated BAEs reduced irrespective of being used as monotherapy 85.65% (p < 0.001) or as an adjuvant therapy 83.71% (p < 0.001) at BRV dosage of 50 to 100 mg BID. This RWE showed the utility of BRV as mono component as an initial add‐on strategy in FoS cases. Significance BRV remains a pertinent therapeutic choice for FoS for the treatment naïve and/or BAE cases. Exposure of LEV leads to considerable BAEs compared to patients without LEV exposure. Patients who switched to BRV due to LEV‐induced BAEs significantly improved tolerability with BRV irrespective being used as monotherapy or as adjuvant therapy. Plain Language Summary Current study was planned to understand the clinical role and relevance of third‐generation anti‐seizure medication (ASM), brivaracetam (BRV) in the real world settings of India. Outcome of the study highlighted that BRV is an emerging, potential and safe ASM treatment option for epilepsy in Indian context. Many patients with epilepsy who are not able to tolerate the other ASM including levetiracetam (LEV) primarily due to behavioral side effects improves tolerability post switch to BRV, additionally results are consistent either BRV being used as an adjuvant therapy or as monotherapy therapy.